MARKETING MIX ANALYSIS OF PATIENT VISITS AT RSGM GUSTI HASAN AMAN - Fatimah Maulideya; Ika Kusuma Wardani; Riky Hamdani; Rosihan Adhani; Fajar Kusuma Dwi Kurniawan (Dentino: Jurnal Kedokteran Gigi, 2024)
Background : Improving public health can be conducted by providing the health service of facilities and infrastructure. RSGM Gusti Hasan Aman becomes the center for the dental and oral health center, especially in the province of South Kalimantan. Based on the patient visit data can be acknowledged that 81% of the patient visit in 2020 and 57,6% in 2022 are patients taken or treated by professional student or young dentists. The different amounts of patients visiting are one of the causes of the less impact of the marketing mix in people that conducted by RSGM Gusti Hasan Aman. Purpose: Analyze marketing mix (product, price, place, promotion, people, process, physical evidence) to patient visits at RSGM Gusti Hasan Aman. Methods: Analytical observational research with cross-sectional research design. The population in this research are outpatients at RSGM Gusti Hasan Aman with a research sample of 107 respondents. Results: The results of the chi-square test on the analysis of the influence of marketing mix, product, price, place, promotion, people, process, and physical evidence affect the level of visits. Conclusion: Increasing the marketing mix in each dimension will raise the number of patient visits in utilizing health services.